Complexifying Roncarelli’s Rule of Law - Leckey, Robert (McGill Law Journal / Revue de droit de McGill, 2010)
The accepted reading of Roncarelli v. Duplessis requires revision. Accounts by which Justice Rand defended the rule of law while the dissenters were indifferent to it mischaracterize the judgment. Justice Rand’s judgment is bolder and less explicit than is typically supposed: his treatment of the notice requirement constitutes part of his defence of the rule of law. For its part, Justice Fauteux’s dissent enacts a plausible understanding of the judge’s role within the rule of law. Disagreement on the overlooked procedural issue is best viewed as fully internal to the rule of law. The judgment’s relevance for rule of law scholars is its exemplification of the possibility for rule of law impulses to conflict, making it a much richer and more interesting text. Scholars’ dismissiveness toward the procedural issue reveals an unsatisfactory view on the part of legal scholars, one by which judges simply apply the rule of law, rather than being also themselves constrained by it.